Conformity between Ileoscopy Appearance with Terminal Ileum Histopathology Appearance in Normal Colonoscopy Chronic Diarrhea Patients - Indra Marki; Ari Fahrial Syam; Irsan Hasan (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Chronic diarrhea is one of the most common problem in gastroenterology cases. Ileoscopy is one of the modalities to determine the etiology of chronic diarrhea by normal colonoscopy appearance. Recently, there is still controversy in the need of this examination in normal macroscopic appearance. The aim of this study is to study the conformity of histopathology abnormalities with ileoscopy appearance in chronic diarrhea patients with normal colonoscopy.Methods: This study uses cross sectional study design by collecting 60 medical record data in several hospitals in Jakarta in the period of 1 January 2005 to 31 December 2011. Diagnostic test between ileoscopy and histopathology is performed by histopathology examination as a gold standard.Results: Study results revealed conformity between both examinations for 93.33%. Sensitivity value of ileoscopy examination compared to histopathology as a gold standard was 94%, specificity 90%, positive predictive value 97.9%, and negative predictive value 75%.Conclusion: Ileoscopy examination in chronic diarrhea patients and normal colonoscopy showed similar results with histopathology examination. Keywords: Ileoscopy, histopathology, conformity, chronic diarrhea